Disordered Ensembles of Strongly Coupled Single-Molecule Plasmonic Picocavities as Nonlinear Optical Metamaterials - Herrera-Urbina, F (American Institute of Physics, 2022)
We propose to use molecular picocavity ensembles as macroscopic coherent nonlinear optical devices enabled by nanoscale strong coupling. For a generic picocavity model that includes molecular and photonic disorder, we derive theoretical performance bounds for coherent cross-phase modulation signals using weak classical fields of different frequencies. We show that strong coupling of the picocavity vacua with a specific vibronic sideband in the molecular emission spectrum results in a significant variation of the effective refractive index of the metamaterial relative to a molecule-free scenario due to a vacuum-induced Autler-Townes effect. For a realistic molecular disorder model, we demonstrate that cross-phase modulation of optical fields as weak as 10 kW/cm2 is feasible using dilute ensembles of molecular picocavities at room temperature, provided that the confined vacuum is not resonantly driven by the external probe field. Our work paves the way for the development of plasmonic metamaterials that exploit strong coupling for optical state preparation and quantum control. © 2022 Author(s).